Morphologic classification of tracheobronchial arborization in children with congenital tracheobronchial stenosis and the associated cardiovascular defects - Hu, Jie; Wang, Hao; Du, Xinwei; Zhu, Limin; Wang, Shunmin; Zhang, Haibo; Xu, Zhiwei; Chen, Hao (Frontiers in Pediatrics, 2023)
Background: We sought to classify patients with congenital tracheal stenosis (CTS) according to tracheobronchial morphology and determine anatomic features associated with tracheobronchial anomalies (TBAs) and concurrent cardiovascular defects (CVDs). Methods: We enrolled 254 patients who underwent tracheoplasty between November 1, 2009 and December 30, 2018. The anatomic features of the tracheobronchial tree and cardiovascular system were abstracted from bronchoscopy, echocardiography, computerized tomography, and operative reports. Results: Four types of tracheobronchial morphology were identified: Type-1, which included normal tracheobronchial arborization (Type-1A, n=29) and tracheal bronchus (Type-1B, n=22); Type-2 (tracheal trifurcation; n=49), and Type-3 (typical bridging bronchus; n=47). Type-4 (bronchus with an untypical bridging pattern) was divided into Type-4A (involving bronchial diverticulum; n=52) and Type-4B (absent bronchus; n=55). Carinal compression and tracheomalacia were significantly more frequent in Type-4 patients than in the other patients (P<0.01). CVDs were common in patients with CTS, especially in patients with Type-3 and Type-4 (P<0.01). Persistent left superior vena cava was most common among patients with Type-3 (P<0.01), and pulmonary artery sling was most frequent among those with Type-4 (P<0.01). Outflow tract defects were most likely to occur in Type-1B. Early mortality was detected in 12.2% of all patients, and young age (P=0.02), operation in the early era (P<0.01), and bronchial stenosis (P=0.03) were proven to be risk factors. Conclusions: We demonstrated a useful morphological classification for CTS. Bridging bronchus was most closely linked with vascular anomalies, while tracheal bronchus was frequently associated with outflow tract defects. These results may provide a clue to CTS pathogenesis.